The short stories - Hughes, Langston, 1902-1967 (Hughes, Langston, 1902-1967. Works. 2001, 2002)
For the first time in many years, Langston Hughes's published collections of stories are now available in a single book. Included in this volume are: Ways of White Folks, originally published in 1934; Laughing to Keep from Crying, originally published in 1952; and additional stories from Something in Common and Other Stories, originally published in 1963; as well as previously uncollected stories. These fictions, carefully crafted in the language Hughes loved, manifest the many themes for which he is best known. We meet and come to know many characters--black and white, young and old, men and women; all as believable as our own families, friends, and acquaintances. Hughes's stories portray people as they actually are: a mixture of good, bad, and much in-between. In these short stories, as in the Simple stories, the reader enjoys Hughes's humor and irony. The stories show us his inclination to mock himself and his beloved people, as much as he ridicules the flaws of those who belittle his race. His genuine characters interact and realistically bring to life this era of America's past. By maintaining the form and format of the original story collections, this volume presents Hughes's stories as he wanted them to be read. This volume will be an invaluable addition to the library of anyone interested in African American literature generally and the fiction of Langston Hughes specifically.